2013
DOI: 10.1016/j.str.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

All-Atom Ensemble Modeling to Analyze Small-Angle X-Ray Scattering of Glycosylated Proteins

Abstract: Summary The flexible and heterogeneous nature of carbohydrate chains often renders glycoproteins refractory to traditional structure determination methods. Small Angle X-ray scattering (SAXS) can be a useful tool for obtaining structural information of these systems. All-atom modeling of glycoproteins with flexible glycan chains was applied to interpret the solution SAXS data for a set of glycoproteins. For simpler systems (single glycan, with a well defined protein structure), all-atom modeling generates mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 69 publications
2
94
0
Order By: Relevance
“…Static light scattering (SLS) and zero-angle intensity from SAXS were used to assess the oligomeric state of each species since these methods have been shown to be accurate for such highly glycosylated proteins (35,46). In addition, dimeric and monomeric gp120 were examined to validate the methods for molecular mass determination (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Static light scattering (SLS) and zero-angle intensity from SAXS were used to assess the oligomeric state of each species since these methods have been shown to be accurate for such highly glycosylated proteins (35,46). In addition, dimeric and monomeric gp120 were examined to validate the methods for molecular mass determination (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular masses were calculated for each sample using the zero angle scattering intensity [I(0)] relative to water or RNase A as a standard (45), with adjustments for carbohydrate content as described previously (46). The particle distance distribution function [P(r)] plot generated from GNOM (44) was used for ab initio shape reconstruction using DAMMIN v5.3i (47).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixing experiments with Gal3 and a bivalent N-glycan in vitro have revealed rapid phase transitions at critical molar ratios between Gal3 and ligands (Ahmad et al, 2004); dynamics are similar to that of phase transitions by adaptor proteins in receptor signaling (Li et al, 2012) or stress-induced RNA-protein granules (Han et al, 2012). N-glycans generally extend away from the protein surface and are flexible due to rotational freedom of the glycosidic bonds (Guttman et al, 2013). Multivalent interactions and a flexible geometry contribute to the intrinsic disorder (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Also small-angle X-ray/neutron scattering and light scattering provide information on the size and shape of the coated proteins,b ut cannot map the conjugation sites. [28,29] More detailed information on the conjugation sites along the primary sequence of the protein can be achieved by mass spectrometry. [27] However,a lso for mass spectrometry the evaluation of the conjugation degree at the different sites in polydisperse populations of isomers is ac hallenge.R ecently,w eh ave shown that structural information on large PEGylated proteins,s uch as E. coli l-Asparaginase-II (138 kDa, ANSII, see the Supporting Information), can be obtained by solid-state NMR spectroscopy.…”
mentioning
confidence: 99%